(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In cognitive pedagogy, the pedagogical foundations of the use of ICT, as well as the study of the negative factors of their impact, are still insufficient, and the level of efficiency of the use of information technologies in the process of creating and presenting scientific and educational information.